Development of a chromatographic method for simultaneous analysis of glutathione forms - Teixeira, Dulce (2019)
Reduced glutathione (GSH)is the most abundant low molecular weight thiol-containing tripeptide (glycine, cysteine, and glutamate) which is synthesized in the cells. GSHplays critical roles in protecting cells from oxidative damage and the toxicity of xenobiotics. Besides, it is also involved in the regulation of intracellular redox homeostasis, which leads to its oxidation into oxidized glutathione (GSSG). Determining the ratio of GSH/GSSG in different biological samples is a major procedure for the evaluation of an individual’s oxidative status and can be a potential biomarker of oxidative stress.